Effect of matrix rigidity on organ-specific capture of tumor cells by flow - Ma, P.; Shen, X.; Tan, P.; Yang, L.; Liu, W. (Cellular and Molecular Biology, 2017)
Accumulating evidences have suggested that tumor metastasis exists prominent organ discrepancy. In this progression, the capture of intravascular tumor cells (TCs) to endothelium in distant tissues and organs plays a decisive role in the organ-specific metastasis formation. However, the mechanism of tumor cells preferentially arrest and adhere to endothelial cells (ECs) of target organ still remains elusive. By using the parallel plate flow chamber and the polyacrylamide gels with different matrix stiffness, we here explored the combined effects of matrix rigidity, shear stress, and chemokine SDF-1 on the capture of circulating tumor cells to ECs in the bloodstream. In addition, the expression and the role of integrin Î²1 on the tumor cells surface were also detected by SDF-1 treatment. The results show that breast tumor cells MDA-MB-231 display an increasing number of adherent cells on the preferred substrate, which is similar to the matrix rigidity of breast cancer tissue (about 5kPa), under a certain shear stress. Moreover, ECs exacerbates the preferred capture of tumor cells compared with the FN-coated substrate alone. Besides, SDF-1 upregulates the number of adherent tumor cells by responding to matrix stiffness via promoting the expression of integrin Î²1, which is abolished by blocking of integrin Î²1. These results may provide a novel point of view for the mechanism of "organ specificity” phenomenon in tumor metastasis, which in turn contribute to a rational development of new drugs for cancer.